Explaining spatial patterns of foreign employment in Germany - Robert Lehmann; Wolfgang Nagl (Regional Studies, 2018)
This paper investigates the main determinants of the representation of foreign employees across German regions. Since migration determinants are not necessarily the same for workers of different nationalities, spatial patterns are explained not only for total foreign employment but also for the 35 most important migration countries to Germany. Based on a total census for all 402 German districts, the paper starts by showing the spatial distributions of workers with different nationalities and explains the emerging patterns by spatial error models. Although large heterogeneity in determinants across nationalities are found, similarities between country groups prevail. Economic conditions matter for most nationalities, whereas the importance of amenities and openness differ.
Keywords: F22; J21; J61; R12; 330; regional foreign employment; migration determinants; spatial models